A Systematic Review of Slash-and-Burn Agriculture as an Obstacle to Future-Proofing Climate Change (The Proceedings of The International Conference on Climate Change, 2020)
The recent haze affecting Malaysia, Indonesia and Singapore, as well as forest fires in the Amazon have raised global concerns on the debilitating effect of slash-and-burn agricultural practice particularly as nations are joining forces in combating climate change. With slash-and-burn still widely practised in the developing nations, this literature review aims to examine the drivers of slash-and-burn agriculture and its impacts in terms of greenhouse gas emissions and atmospheric CO2 sequestration, while suggesting alternatives to slash-and-burn agriculture. The review covers more than 80 articles on slash-and-burn agriculture, published mainly over the past 15 years. Slashand-burn agriculture has been survived by the pressure to make a living under inadequate resources, access to market and technologies, a lack of alternative livelihoods as well as loopholes in institutional mechanisms, regulations and enforcement. Slash-and-burn agriculture leads to chemical changes of soil, alteration of soil biota and species richness, and the extent of changes correlates with fallow period after slash-and-burn. Large-scale slash-and-burn for commercial agriculture and livestock farming is the major contributor of greenhouse gases and agricultural intensification shortens fallow period for recovery of ecosystems. Slash-and-burn also impacts the ability of forests to sequester atmospheric CO2 and short fallow period further reduces this ability. This review calls for alternative agricultural practices comprising two approaches namely land preparation and landuse systems, as adaptation and mitigation against climate change. Land preparation consists of mulching, improved forest conversion, mechanized land preparation and slash-and-char system.Land-use systems however are categorized into alternative agrosystems, agroforestry, cultivated pastureland and integrated system of crop-livestock-forests. This review therefore contributes to raising awareness and proposing practical alternatives to slash-and-burn for environmental sustainability.
Keywords: agriculture; climate change; greenhouse gases; slash-and-burn